The Development of TANAKA Android-based Application as an Information Media for Taka Bonerate National Park - Amelia Firdhausya Dewi; Deviv, Selvia; Munir, Nur Syamsinar (Ceddi Journal of Education, 2023)
This research aims to implement an interactive multimedia application using Unity software on a desktop platform, specifically designed to introduce short surahs from Juz Amma to students, with a focus on Datok Sulaiman Putra Islamic Preschool in Palopo City. This research is motivated by the need for innovative and engaging methods to enhance the learning experience of preschool students in Islamic education. The research follows the Multimedia Development Life Cycle (MDLC) and incorporates methods such as observation, interviews, and literature studies, including direct observation for data collection. The testing technique employed is Usability Testing, which aims to assess the user-friendliness and ease of use of the multimedia application. The results of this research, from the implemented application, can facilitate the process of introducing short chapters from Juz Amma, making it easier for students to read and understand them in the Qur'an. This research provides benefits in the development of interactive educational tools that can significantly contribute to the learning journey of preschool students in Islamic education.